The Mediating Role of Job Satisfaction in The Effect of Perceived Organizational Support on Employee Organizational Commitment at The Trans Resort Bali - I Made Agus Yona Surya Andika; Ni Wayan Mujiati (International Journal of Economics, Management and Accounting, 2025)
One of the key factors in a company’s success is its human resources, particularly employees who are committed to fulfilling their responsibilities within the organization. This study aims to analyze the mediating role of job satisfaction in the effect of perceived organizational support on the organizational commitment of employees at The Trans Resort Bali. The study involved a sample of 59 employees. The sampling method used was proportional stratified random sampling. Data were collected through the distribution of questionnaires. The analysis technique employed in this study was Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) approach. The results indicate that perceived organizational support has a positive and significant effect on organizational commitment. Perceived organizational support also has a positive and significant effect on job satisfaction. Furthermore, job satisfaction positively and significantly affects organizational commitment. Job satisfaction is proven to positively mediate the effect of perceived organizational support on organizational commitment.